Tax practitioners' acceptance of electronic tax filing system Sabah and Sarawak: survey evidence/ Noraini Edris - Edris, Noraini (2006)
Experiences from overseas countries that had implemented an electronic tax filing system (e-filing) indicated that tax practitioners play an important role in the diffusion of the tax technology. In Malaysia, e-filing is at its early stage of implementation, thus far, little is known about the tax practitioners' acceptance of new tax technology. The study aims (i) to examine the determinants of tax practitioners' acceptance of an e-filing system; (ii) to evaluate the importance of several types of incentives that will motivate the tax practitioners to use e-filing; and (iii) to study other considerations towards the acceptance of e-filing. A mail survey was used to collect data. Questionnaire was posted to 364 tax practitioners in Sabah and Sarawak. Ninety-two (92) usable questionnaires were received; the response rate was about 25% (92/364). The survey found that perceived usefulness had a positive effect on tax practitioners' usage intention of the e-filing system. Overall, 37% of the variance of tax practitioners' usage intention of the e filing system can be explained by the proposed integrated technology acceptance model. The survey also uncovered that the quest for speedy tax refund and speedy feedback are the key incentives that would motivate tax practitioners to use e-filing. However, concern over cost of compliance, not being user friendly, confidentiality, privacy, reliability and stability of the e-filing system were the major impediments to use the technology. The findings suggest that tax authorities ought to make sure that e-filing system is useful for tax practitioners in enhancing their tax service quality, and to incorporate American Institute of Certified Accountants (AICPA) (2001)'s guiding principles in developing e-filing policies in order to accelerate the diffusion of e-filing system.